EXEMPTION OF THE SELLER UNDER ART. 80 OF THE UN CONVENTION ON CONTRACTS FOR THE INTERNATIONAL SALE OF GOODS - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Seller's breach of delivery obligation will render him liable and a range of remedies will be available to the buyer pursuant Art. 45 of the CISG. However, the buyer may not rely on a seller’s failure to perform delivery to the extent that such a failure was caused by his own act or omission. Art. 80 of the CISG represents the concretisation of the principle of good faith from Art. 7(1) of the CISG. Art. 80 of the CISG has a distinctive sphere of application in comparison to the Art. 79 of the CISG and represents independent legal ground for exemption of the seller for the non-delivery. The provision requires that the failure to deliver the goods has been caused by the buyer’s own act or omission. It is applicable not only when the buyer solely causes non-delivery, but also in cases of shared responsibility i.e. when seller’s failure to perform is caused by both parties. However, Art. 80 does not provide much guidance for the complex situations where both parties have caused breach of the delivery obligation.